The role of naftopidil in the management of benign prostatic hyperplasia - Hara, Noboru (SAGE Publications, 2013)
Naftopidil, which to a certain extent shows an affinity to α(1D)-adrenoceptor subtype in addition to a high affinity to α(1A)-adrenoceptor, has been used for the treatment of benign prostatic obstruction and benign prostatic hyperplasia (BPH) associated lower urinary tract symptoms (LUTS). The aim of the present review is to systematically refer to the published studies on this unique agent for BPH. Based on a randomized prazosin-controlled study and another double-blind placebo-controlled study, which verified the dose-dependent effects of naftopidil, the Japanese Ministry of Health, Labor and Welfare approved naftopidil for treating men with BPH in 1996. Several tamsulosin-controlled studies have suggested treatment effects of naftopidil similar to those of tamsulosin and potentially higher efficacy for alleviating storage symptoms by naftopidil. Although well-designed, randomized studies are warranted to confirm the long-term outcomes and effector/target of naftopidil, the α(1A)-antagonist naftopidil, which also blocks α(1D)-adrenoceptor, improves voiding symptoms, and may also be useful for the management of men with storage symptoms represented by nocturia, retrieving their quality of life impaired by BPH-associated LUTS.